Recruitment in Recovery - Mark Sanders; R. Welters (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2009)
Burgess (1993) finds that job finding rates for the unemployed do not move proportionately to changes in the overall hiring rate. Burgess hints at employed job seekers that start looking in tight conditions and crowd out the unemployed. But he leaves the search behaviour of firms unaddressed. Russo et al. (2000) and Russo et al. (2001), however, shows that firms switch their preferred recruitment channel in changing labour market conditions. We introduce recruitment channels in a search model and find an additional mechanism through which the unemployed obtain less than their 'fair share' of the job offers. We then test our model's predictions using panel data from the Netherlands and find support for this hypothesis.
Keywords: 330; employer search; job search; recruitment channels; tightness